the Number Of Human Society Informedia And Mechanics In The Shadow Of The New Media - بخاري حفيظة (International Journal of Social Communication, 2014)
Abstcrat : Communication technology is in an endless dynamic and evolution, in a way that has forced the human being to change in every moment and every second, and to continually forge renewable terms overnight, only to keep up with the stakes of the time he lives, from the term of the fifth Revolution, to the post-modern era, Then the information age, many conventions have been eroded, to be replaced by new others.